Day 2 Wed, February 10, 2016 2016
DOI: 10.2118/179136-ms
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of Completion Effectiveness in Hydraulically Fractured Wells and the Assessment of Refracturing Scenarios

Abstract: For refracturing candidate selection, good reservoir understanding and a thorough evaluation of completion effectiveness is necessary to help minimize risk. However, this task can be difficult because of various uncertainties in terms of reservoir characterization and completion evaluation procedures.Failure to identify damage mechanisms when evaluating potential refracturing candidates can cause varying success rates and often minimal incremental recovery or marginal economics. Stimulation effectiveness is of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Comparing the effects of refracturing at different initial fractures shows that the cumulative gas production from wells with a big initial fracture spacing is similar to that from wells with a small initial fracture spacing if the final fracture spacing is the same. Dahl et al [7] analyzed the influence of both the reservoir and fracture parameters (fracture length, width and number of fractures) on the effects of a refractured well in the Eagle Ford Shale. They found that the shale gas production after 10 years still increases with new fractures.…”
Section: Introductionmentioning
confidence: 99%
“…Comparing the effects of refracturing at different initial fractures shows that the cumulative gas production from wells with a big initial fracture spacing is similar to that from wells with a small initial fracture spacing if the final fracture spacing is the same. Dahl et al [7] analyzed the influence of both the reservoir and fracture parameters (fracture length, width and number of fractures) on the effects of a refractured well in the Eagle Ford Shale. They found that the shale gas production after 10 years still increases with new fractures.…”
Section: Introductionmentioning
confidence: 99%